Environmental Education in Polish Schools: Current Challenges, Practices and Future Pathways - Mazur, Zbigniew; Tkaczenko, Halina; Kurhaluk, Natalia (Theoretical and Methodical Problems of Children and Youth Education, 2025)
This article analyses the state of environmental education in the Polish school system, emphasising its importance and highlighting existing problems and opportunities for development. Although pro-environmental content is included in the core curriculum, mainly within natural science subjects, the article emphasises that environmental education is implemented in a fragmented and unsystematic manner. The main barriers to effective implementation are the absence of a dedicated subject, limited teacher training, underutilisation of available teaching resources, and low ecological awareness among students and teachers. The analysis concludes that environmental education should be interdisciplinary and practiceoriented, incorporating field projects, outdoor activities, collaboration with local communities, and familyoriented initiatives. Non-governmental organisations play an important role by offering valuable initiatives, but their reach remains limited. At the same time, environmental education needs to be integrated with broader sustainability agendas, such as the United Nations Sustainable Development Goals (SDGs), to ensure coherence between national practices and global priorities. Improving the situation requires coherent educational policies, teacher training and support, the integration of teaching materials into the curriculum, and strengthened partnerships between schools, institutions, and NGOs. An analysis of international practices, such as the Slovak model, indicates that introducing additional subjects or educational pathways in ecology can significantly improve teaching effectiveness. In conclusion, the article argues that improving the effectiveness of environmental education requires a holistic, systemic approach that combines coherent educational policy, adequate funding, professional support for teaching staff, and close cooperation between schools, institutions, and the local community.